(untitled) (JED (Jurnal Etika Demokrasi), 2026)
Early childhood teacher competency remains a critical issue in efforts to improve the quality of early childhood education, particularly because teachers are central to children’s cognitive, social, emotional, and moral development. Principal leadership is widely recognized as a strategic factor in strengthening teacher professionalism; however, empirical findings on its role in developing early childhood teacher competency remain fragmented across studies. This study aims to analyze the role of principal leadership in improving early childhood teacher competency and to identify leadership strategies that are most effective in supporting teacher professional development. This study employed a systematic literature review with a descriptive synthesis approach. The data sources consisted of nine peer-reviewed scientific articles indexed in SINTA 2 and SINTA 3, published between 2019 and 2025, and retrieved through Google-based searches. Article selection was conducted using predetermined inclusion and exclusion criteria, while data were analyzed through systematic content analysis to identify recurring themes, leadership roles, and strategic patterns. The findings indicate that principals contribute to teacher competency development through their roles as academic supervisors, motivators, facilitators, instructional leaders, transformational leaders, servant leaders, empowering leaders, and collaborative leaders. The most prominent strategies include academic supervision, technology-based supervision, teacher empowerment, continuous professional development, workshop facilitation, learning communities, performance evaluation, and the creation of a collaborative and supportive work climate. This study concludes that effective principal leadership substantially enhances early childhood teacher competency and contributes to improved learning quality. The novelty of this study lies in its systematic synthesis of leadership roles and strategies specifically within early childhood education. The findings contribute to educational leadership scholarship and provide practical guidance for policy formulation, school leadership development, and teacher competency improvement programs.